Regional variations in excessive polypharmacy and potentially inappropriate drug use among older adults in Sweden: Trends from 2006 to 2020 - Wastesson, Jonas W.; Fritzell, Johan; Burström, Bo; Johnell, Kristina; Fastbom, Johan (Frontiers in Pharmacology, 2023)
INTRODUCTION Potentially inappropriate drug use (PID) is common among older adults. Cross-sectional data suggest that there are marked regional variations in PID in Sweden. There is, however, a lack of knowledge about how the regional variation have changed over time. OBJECTIVES This study aimed to investigate the regional differences in the prevalence of PID in Sweden, 2006-2020. METHODS In this repeated cross-sectional study, we included all older adults (≥75 years) registered in Sweden, yearly from 2006 to 2020. We used nationwide data from the Swedish Prescribed Drug Register linked at the individual level to the Swedish Total Population Register. We selected three indicators of PID according to the Swedish national ‘Quality indicators for good drug therapy in the elderly’: 1) Excessive polypharmacy (use of ≥10 drugs); 2) Concurrent use of three or more psychotropic drugs; 3) Use of ‘drugs that should be avoided among older persons’. The prevalence of these indicators was calculated for each of Sweden’s 21 regions, yearly from 2006 to 2020. The annual coefficient of variation (CV) was calculated for each indicator by dividing the standard deviation of the regions by the national average, to measure relative variability. RESULTS In the population of about 800,000 older adults per year, the national prevalence of ’drugs that should be avoided by older adults’, was reduced by 59% from 2006 to 2020. There was a slight decline in the use of three or more psychotropics, while the prevalence of excessive polypharmacy increased. The CV for excessive polypharmacy was 14% in 2006 and 9% in 2020 compared to 18% and 14% for ‘use of three or more psychotropics’, and stable at around 10% for ‘drugs that should be avoided in the elderly’. CONCLUSIONS The regional variation in potentially inappropriate drug use decreased or were stable from 2006 to 2020. The regional differences were largest for the use of three or more psychotropics. We found a general tendency that regions with a good performance at the start of the period performed well across the entire period. Future studies should investigate the reasons for regional variation and explore strategies to reduce unwarranted differences.